THE EFFECT OF EMPOWERMENT AND EMPLOYEE ENGAGEMENT ON JOB SATISFACTION, ORGANIZATIONAL COMMITMENT AND ITS IMPACT ON PERFORMANCE OF PTPN V - Dedi Sulistiono; Aji Hermawan; Anggraini Sukmawati (School of Business, Bogor Agricultural University (SB-IPB), 2019)
The study aims to test and empirically prove the effect of empowerment and employee engagement on job satisfaction and organizational commitment and its impact on performance at PT Perkebunan Nusantara V. The study focused on employees who worked in the plantation area, especially those in the afdeling PT Perkebunan Nusantara V Riau. Afdeling or division is the smallest unit of the plantation management, which is an administrative area that manages agronomic plantations with an area of between 500-1000 hectares. The sample in this study were 360 respondents who are staff employees and non-staff employees at the supervisor level. The research sample was taken by purposive sampling. Data was collected by providing questionnaires and interviews, then analyzed using descriptive analysis and processed using the Structural Equation Model (SEM) with Partial Least Square (PLS) programs. The latent variables in this study are empowerment, employee engagement, job satisfaction, organizational commitment and performance. The results of this study indicated that: (1) empowerment has no significant effect on job satisfaction (2) empowerment has no significant effect on organizational commitment; (3) employee engagement has a significant effect on job satisfaction (4) employee engagement has a significant effect on organizational commitment; (5) job satisfaction has no significant effect on performance; and (6) organizational commitment has no significant effect on performance. Keywords: empowerment, employee engagement, job satisfaction, organizational commitment, performance